Simultaneous adsorption of cationic dyes from binary solutions by thiourea-modified poly(acrylonitrile-co-acrylic acid): detailed isotherm and kinetic studies - Adeyi, Abel Adekanmi; Md. Jamil, Siti Nurul Ain; Abdullah, Luqman Chuah; Choong, Thomas Shean Yaw; Lau, Kia Li; Abdullah, Mohammad (MDPI, 2019)
In this study, simultaneous adsorption of cationic dyes was investigated by using binary component solutions. Thiourea-modified poly(acrylonitrile-co-acrylic acid) (TMPAA) polymer was used as an adsorbent for uptake of cationic dyes (malachite green, MG and methylene blue, MB) from aqueous solution in a binary system. Adsorption tests revealed that TMPAA presented high adsorption of MG and MB at higher pH and higher dye concentrations. It suggested that there are strong electrostatic attractions between the surface functional groups of the adsorbent and cationic dyes. The equilibrium analyses explain that both extended Langmuir and extended models are suitable for the description of adsorption data in the binary system. An antagonistic effect was found, probably due to triangular (MG) and linear (MB) molecular structures that mutually hinder the adsorption of both dyes on TMPAA. Besides, the kinetic studies for sorption of MG and MB dyes onto adsorbent were better represented by a pseudo-second-order model, which demonstrates chemisorption between the polymeric TMPAA adsorbent and dye molecules. According to experimental findings, TMPAA is an attractive adsorbent for treatment of wastewater containing multiple cationic dyes.